Direct HST Dust Lane Detection in Powerful Narrow-Line Radio Galaxies - Ramírez, Edgar A.; Aretxaga, Itziar; Tadhunter, Clive N.; Lopez-Rodriguez, Enrique; Packham, Chris (Frontiers in Astronomy and Space Sciences, 2017)
We present the analysis of near-infrared Hubble Space Telescope imaging of 10 Fanaroff Riley II powerful radio galaxies at low redshift (0.03<z<0.11) optically classified as narrow-line radio galaxies. The photometric properties of the host galaxy are measured using Galfit, and compered with those from the literature. Our high resolution near-infrared observations provide new and direct information on the central kpc-scale dust lanes in our sample that could be connected to the pc-scale torus structure. Moreover, analyzing the infrared spectrograph Spitzer spectra of our sample, we suggest properties of the dust size of the torus}.